Literature Review: The Effect of Puskesmas Accreditation Status on Patient Satisfaction with Service Quality as an Intervening Variable - Suwandi, Suwandi; Hikma, Nur; Yudit, Yudit; Sudirman, Sudirman; Yani, Ahmad (Devotion : Journal of Research and Community Service, 2025)
a